2013
DOI: 10.1002/jbm.a.34644
|View full text |Cite
|
Sign up to set email alerts
|

Patterned CoCrMo and Al2O3 surfaces for reduced free wear debris in artificial joint arthroplasty

Abstract: Surface wear of corresponding tribological pairings is still a major problem in the application of artificial joint surgery. This study aims at developing wear reduced surfaces to utilize them in total joint arthroplasty. Using a pico-second laser, samples of medical CoCrMo metal alloy and Al2 O3 ceramic were patterned by laser material removal. The subsequent tribological investigations employed a ring-on-disc method. The results showed that those samples with modified surfaces show less mass or volume loss t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…A deep dimple can be utilized as a reservoir of microsized wear debris. The previous studies indicate that nanosized wear debris is more biologically active especially when under ionized conditions . Therefore, we predict that trapped wear debris into the dimples will be less biologically reactive to the surrounding tissue thus improving the acceptability.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…A deep dimple can be utilized as a reservoir of microsized wear debris. The previous studies indicate that nanosized wear debris is more biologically active especially when under ionized conditions . Therefore, we predict that trapped wear debris into the dimples will be less biologically reactive to the surrounding tissue thus improving the acceptability.…”
Section: Resultsmentioning
confidence: 82%
“…For example, Amanov and Sasaki reported that Cr‐doped DLC‐coated dimpled specimen exhibited a lower friction coefficient (>50%) and wear rate (>50%) when compared with those of their polished counterparts under oil‐lubricated sliding conditions; this was achieved by the combination of the storage of wear debris in the dimples and having high hardness of the DLC layer. Tarabolsi et al also reported that microdimpled CoCrMo and Al 2 O 3 surfaces significantly reduced the amount of wear debris in artificial joint arthroplasty. However, the combination of microdimple and hard coating such as DLC has not been investigated to the artificial hip joints yet.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Additionally, electrochemical measurements outlined that the textured surfaces (dimple design) did not affect the corrosion potential of the metal-on-polyethylene (MoP) bearing [17]. It can also be added that these textures can act as wear traps for particles and subsequently improve the life cycle of artificial joints [18][19][20].…”
Section: Introductionmentioning
confidence: 99%